2016
DOI: 10.28945/3520
|View full text |Cite
|
Sign up to set email alerts
|

Genetic-linked Inattentiveness Protects Individuals from Internet Overuse: A Genetic Study of Internet Overuse Evaluating Hypotheses Based on Addiction, Inattention, Novelty-seeking and Harm-avoidance

Abstract: The all-pervasive Internet has created serious problems, such as Internet overuse, which has triggered considerable debate over its relationship with addiction. To further explore its genetic susceptibilities and alternative explanations for Internet overuse, we proposed and evaluated four hypotheses, each based on existing knowledge of the biological bases of addiction, inattention, novelty-seeking, and harm-avoidance. Four genetic loci including DRD4 VNTR, DRD2 Taq1A, COMT Val158Met and 5-HTTLPR length polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 136 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…Specifically, we found no association between the 5-HTTPR polymorphism and IA. Previous studies [ 36 , 41 ] have reported that the S/S genotype HTTLPR increased the risk of IA. Similarly, our study indicated a higher percentage of the S/S genotype in the IA group than in the control group, but there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, we found no association between the 5-HTTPR polymorphism and IA. Previous studies [ 36 , 41 ] have reported that the S/S genotype HTTLPR increased the risk of IA. Similarly, our study indicated a higher percentage of the S/S genotype in the IA group than in the control group, but there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has a polymorphic 48-base pair VNTR in exon 3, and the most frequent polymorphisms are 4 (4R), 7 (7R), and 2 (2R) repeats [ 33 ]. Previous studies have underlined significant associations between the DRD4 4R genotype with increased attentiveness [ 34 , 35 ] that, in turn, has been associated with a higher risk of IA [ 36 ]. Besides the role played by dopamine, it has been evidenced that serotonin may also be implicated in IA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the other study demonstrated that the overall use of the Internet is greatly affected by one's ability to sustain attention. Carriers of the alleles associated with decreased attentiveness (DRD4 2R and 7R, 5-HTTLPR long) are protected from Internet overuse (Sun & Spathis, 2016).…”
Section: Polymorphism Gene In Internet Addictionmentioning
confidence: 99%